3D printed silicon-few layer graphene anode for advanced Li-ion batteries. Issue 56 (29th October 2021) - Beydaghi, Hossein; Abouali, Sara; Thorat, Sanjay B.; Del Rio Castillo, Antonio Esau; Bellani, Sebastiano; Lauciello, Simone; Gentiluomo, Silvia; Pellegrini, Vittorio; Bonaccorso, Francesco
Abstract : Novel 3D printed anodes based on Si and wet-jet milling-exfoliated few-layer graphene are produced by fused diffusion modelling (FDM) technique and used in Li-ion batteries. Abstract : The printing of three-dimensional (3D) porous electrodes for Li-ion batteries is considered a key driver for the design and realization of advanced energy storage systems. While different 3D printing techniques offer great potential to design and develop 3D architectures, several factors need to be addressed to print 3D electrodes, maintaining an optimal trade-off between electrochemical and mechanical performances. Herein, we report the first demonstration of 3D printed Si-based electrodes fabricated using a simple and cost-effective fused deposition modelling (FDM) method, and implemented as anodes in Li-ion batteries. To fulfil the printability requirement while maximizing the electrochemical performance, the composition of the FDM filament has been engineered using polylactic acid as the host polymeric matrix, a mixture of carbon black-doped polypyrrole and wet-jet milling exfoliated few-layer graphene flakes as conductive additives, and Si nanoparticles as the active material. The creation of a continuous conductive network and the control of the structural properties at the nanoscale enabled the design and realization of flexible 3D printed anodes, reaching a specific capacity up to ∼345 mA h g −1 at the current density of 20 mA g −1, together with a capacity retention of 96% after 350 cycles. The obtained results are promising for the fabrication of flexible polymeric-based 3D energy storage devices to meet the challenges ahead for the design of next-generation electronic devices.